Apigenin inhibits NLRP3 inflammasome activation in monocytes and macrophages independently of CD38 - Lauritzen, Knut Husø; Yang, Kuan; Frisk, Michael; Louwe, Mieke C.; Olsen, Maria Belland; Ziegler, Mathias; Louch, William E.; Halvorsen, Bente; Aukrust, Pål; Yndestad, Arne; Sandanger, Øystein (Frontiers in Immunology, 2025)
IntroductionCD38, a regulator of intracellular calcium signalling, is highly expressed in immune cells. Mice lacking CD38 are very susceptible to acute bacterial infections, implicating CD38 in innate immune responses. The effects of CD38 inhibition on NLRP3 inflammasome activation in human primary monocytes and monocyte-derived macrophages have not been investigated. Apigenin is a naturally occurring flavonoid known to inhibit CD38. However, apigenin has also been proposed to inhibit the extracellular ATP receptor P2XR7, an upstream activator of NLRP3. In this study we aimed to investigate whether apigenin attenuates NLRP3 inflammasome activation in human monocytes and monocyte-derived macrophages through CD38 inhibition. MethodsLPS-primed human monocytes and monocyte-derived macrophages were treated with apigenin, the CD38 inhibitor 78c, antagonists of CD38 second messengers (8-br-ADPR and 8-br-cADPR) or the ATP hydrolase, apyrase, prior to NLRP3 activation with ATP, monosodium urate crystals (MSU) or nigericin. IL-1β and TNF secretion and mRNA expression, as well as N-terminal gasdermin-D formation were quantified. Ca2+ mobilization was determined by live confocal microscopy. NLRP3 activity was also compared in WT and CD38-/- mouse bone marrow-derived macrophages (BMDMs) with and without CD38 inhibitors.ResultsApigenin significantly inhibited IL-1β release from LPS-primed monocytes and macrophages activated with ATP, MSU, or nigericin. CD38 inhibition with 78c also attenuated NLRP3-dependent IL-1β release. Apigenin was a potent inhibitor of Ca2+ flux from the endoplasmic reticulum to the cytosol in human monocyte-derived macrophages. Apyrase attenuated IL-1β release induced by ATP or MSU, but not by nigericin. However, the NLRP3 inflammasome is not compromised in CD38-/- bone marrow-derived macrophages compared to corresponding WT cells, and apigenin moderated IL-1β release in both genotypes. DiscussionOur data support that apigenin attenuates NLRP3 activation independently of CD38. Our results also suggest that MSU crystals activate NLRP3 through autocrine or paracrine ATP signalling.